Mapping agrarian livelihood asset accessibility in the state of West Bengal, India - Priyanka Das; Shikha Singh; Lucky Sharma (National Geographical Journal of India, 2025)
Farmers’ welfare is critical for achieving food security, rural resilience, and equitable development, especially in agriculturally dominant states such as West Bengal, where a large share of the population relies on farming and allied sectors. Anchored in the Sustainable Livelihood Framework (DFID, 1999; Chambers & Conway, 1992), this study focuses on understanding district-wide disparities in farmers’ access to livelihood resources—interpreted through five foundational capitals: natural, physical, human, financial, and social. However, to better contextualize livelihood assessment within the agrarian domain, the study draws upon the approach of Satyasai (2021), who proposed a redistribution of livelihood assets into six policy-relevant and sector-specific dimensions: Production, Post-Production, Infrastructure, Social Development, Ecological Aspects, and Policy and Fiscal Environment. This restructured lens enables a more nuanced evaluation of the accessibility and adequacy of livelihood provisioning in agriculture. Accordingly, the study employs 29 indicators spanning these six dimensions to construct the Agrarian Livelihood Asset Accessibility Index (ALAAI), using government reports and agricultural surveys. The data of six dimension was normalized and aggregated to produce sub-indices which are further integrated to from a composite index called Agrarian Livelihood Asset Accessibility Index (ALAAI) using equal weighted approach. The findings indicate that Bardhaman has the highest ALAAI score (0.58), while Darjeeling scores the lowest (0.17), signifying urgent needs for targeted interventions in lower-scoring districts. A coefficient of variation analysis was conducted to understand the extent of variation among districts, revealing significant disparities in agricultural development. Overall, this study emphasizes the importance of comprehensive policies and focused investments to enhance farmers’ welfare, address regional disparities, and promote sustainable agricultural development in West Bengal.